2015
DOI: 10.1111/avj.12315
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective survey of bronchoalveolar lavage fluid cytology in Western Australian horses presented for evaluation of the respiratory tract: effect of season on relative cell percentages

Abstract: In this study, a relative mast cell increase was the most common cytological profile in horses with lower airway inflammation and was associated with season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The percentage of horses diagnosed with mild equine asthma using classification one (lower cut off percentages) and the type of cellular response observed in this study were consistent with a previous Australian study that used a similar airway sampling technique . Similar to the findings of that study, a mixed mastocytic response was the most common BALF cytological abnormality in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The percentage of horses diagnosed with mild equine asthma using classification one (lower cut off percentages) and the type of cellular response observed in this study were consistent with a previous Australian study that used a similar airway sampling technique . Similar to the findings of that study, a mixed mastocytic response was the most common BALF cytological abnormality in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Some recent reports and a revised consensus statement in 2016 raised the clinically relevant cut‐off of metachromatic cells to 5% . Reassignment of the cut‐off value has not been supported by pulmonary function testing, and a recent epidemiological study did not identify any horse characteristics or current or historical clinical findings that would differentiate horses with mast cells > 5%, compared to horses with between 2 and 5% . Another recent study assessing performance suggests the cut‐off values for mast cells should be between 2 and 3% …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The cytological definition of IAD has been the subject of much debate and recommended reference values for abnormal percentages of inflammatory cells in BALF have been recently revised . Our group has concluded that geographic location influences the predominant abnormal cytological profile in symptomatic horses . The extrapolation of normal values derived from groups of horses in different geographic locations may have little relevance to local populations.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate history and clinical findings can confer a high level of suspicion of IAD, but demonstration of non-septic inflammation within bronchoalveolar lavage fluid (BALF) and/or pulmonary function testing is needed to confirm the diagnosis. 4 Researchers at Murdoch University veterinary hospital retrospectively reviewed the case records of horses with suspected IAD to characterise BAL cytological profiles and investigate if these were affected by season, horse characteristics or presenting clinical problem(s). The results showed that approximately 70% of horses had non-infectious lower airway inflammation as defined by abnormal BALF cytology, although this was not associated with history or clinical examination and endoscopy findings, with the exception of nasal discharge.…”
mentioning
confidence: 99%